1998
DOI: 10.1037/0022-0663.90.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Supporting visual and verbal learning preferences in a second-language multimedia learning environment.

Abstract: English-speaking college students who were enrolled in a German course read a 762-word German language story presented by a computer program. For key words in the story, students could choose to see a translation on the screen in English (i.e., verbal annotation) or view a picture or video clip representing the word (i.e,, visual annotation), or both. Students remembered word translations better when they had selected both visual and verbal annotations during learning than only 1 or no annotation; students com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
248
2
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 362 publications
(265 citation statements)
references
References 42 publications
(58 reference statements)
9
248
2
6
Order By: Relevance
“…Plass, Chun, Mayer, and Leutner (1998) found that visualizers were more effective in using visual cues for remembering words, whereas verbalizers were more effective in using verbal cues. Furthermore, visualizers performed better on propositions with both verbal and visual annotations than on verbal annotations alone, but verbalizers performed well on both types.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Plass, Chun, Mayer, and Leutner (1998) found that visualizers were more effective in using visual cues for remembering words, whereas verbalizers were more effective in using verbal cues. Furthermore, visualizers performed better on propositions with both verbal and visual annotations than on verbal annotations alone, but verbalizers performed well on both types.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Multiple presentation modes may be particularly important for students with disabilities such as hearing impairments, although only regular education students were involved in our research. The importance of accommodating individual differences in learning style has long been recognized in educational psychology (Jonassen & Grabowski, 1993) and has been tested in a multimedia learning environment (Plass, Chun, Mayer, & Leutner, 1998). The information delivery hypothesis predicts that adding on-screen text to a narrated animation will result in better performance on tests of learning that focus on remembering the verbal explanation (i.e., retention test) and being able to use the explanation to solve new problems (i.e., transfer test).…”
Section: Methodsmentioning
confidence: 99%
“…However, these results should not be taken to deny the value of allowing learners some choice in adjusting multimedia presentations to fit their learning preferences in all situations. In fact, a better pedagogical approach may be to allow learners to choose whether they would prefer to see words as on-screen text or hear words as narration rather than presenting words in both forms (Plass et al, 1998).…”
Section: Theoretical Implications Of the Redundancy Effectmentioning
confidence: 99%
“…As it is depicted, there was not a prominent difference between the performances of the groups on the post-reading [F Table 4.18). However, there is a significant difference between the performances of the groups on the post-anxiety [F (1,47) Based on the Table 10, the experimental group's adjusted mean scores on post-reading, post-vocabulary, and postanxiety are 25.138, 30.170, and 51.114 respectively; while those of the control group are 23.939, 28.830, and 61.579 respectively. Since the control group's adjusted mean score (61.579) on the post-anxiety was very higher than that (51.114) of the experimental group, this implies that independent variable (reader-response approach) lowered the participants' test anxiety in the experimental group.…”
Section: Resultsmentioning
confidence: 99%